Correlation between Peak Left Atrial Longitudinal Strain and The Severity of Mitral Valve Disease at Haji Adam Malik General Hospital Medan - Ryanti, Dina; Ketaren, Andre Pasha; Muhktar, Zulfikri; Akbar, Nizam Zikri; Lubis, Anggia Chairuddin; Ardini, Tengku Winda (The Indonesian Heart Association, 2025)
In “Correlation between Peak Left Atrial Longitudinal Strain and The Severity of Mitral Valve Disease at Haji Adam Malik General Hospital Medan” (Indonesian Journal of Cardiology, 44(2), 68-74. https://doi.org/10.30701/ijc.1541), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1541. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error. DOI of original article: https://doi.org/10.30701/ijc.1541